Leaflet - TUC/Labour Party United against racialism, 1978 (1978)
1978 "Leaflet - TUC/Labour Party United against racialism, 1978" [T0421.jpg], 1978 This leaflet, 'The National Front is a Nazi Front: the TUC - Labour Party united against racialism' was issued in 1978